PEMBERDAYAAN PETANI ARAK DI DESA TRI EKA BUANA, KECAMATAN SIDEMEN, KABUPATEN KARANGASEM MELALUI PERATURAN GUBERNUR BALI NO.1 TAHUN 2020 - Surya Dharma, I Gede Bagus Raditya; Punia, I Nengah; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 01 (2021): JISSOROT, 2021)
Arak is a beverage that is distilled from rice, palm sap and others which is then fermented so that it becomes a processed alkoholic beverage. Tri Eka Buana Village in Sidemen District, Karangasem Regency.The concept of power (daya) explains how arak farmers in Tri Eka Buana village get power (strength) from the issuance of Bali Governor Regulation . The concept of The Disadvantage (Inequality) is used to examine how the Governor of Bali Regulation No. 1 of 2020 is able to reduce the inequality that occurs in the community, especially The Joint Prosperity Cooperative of Traditional Village Farmers or KBS-Padat is an implementation of this governor's regulation to improve arak farmers in Tri Eka Buana village with training and forms of marketing cooperation. Keywords: Community Empowerment, Bali Governor Regulation No.1 of 2020, Arak, Tri Eka Buana Village, Power, The Disadvantage